A Review: Performance Enhancement in Wireless Network by Considering Attenuation Factors - Er. Sheenu Sachdeva,; Luxmi Sharma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In this day and age, there is an ever-increasing need for wireless communication. There is a substantial amount of work that has to be done in the field of wireless communication. In the context of cloud computing and Internet of Things technologies, wireless connectivity has been utilized rather often. As a result, there is a need to find a solution in order to obtain the optimal configuration of wireless communication in order to experience the least amount of attenuation. Present paper is considering the factors that influencing the performance of wireless network. Major factor, that is influencing quality of service in wireless network is attenuation. This paper is reviewing the existing research that are considering attenuation factors. Present research is focused on Radio over Fiber Technology (RoF) and considering its architecture.
Keywords: Wireless network; attenuation; Radio over Fiber Technology